Impact of an education programme on the control and prevention of soil-transmitted nematode infections. - Karunaratne, V (My University, 1992)
The main objective of this study was to determine the impact of an education programme on the control and prevention of soil- transmitted nematode infections among school children. This study has shown that, the education programme carried out for the student s did have an impact on the reduction of fresh infection, re-infection as well as prevalence rates of ascaris among school children.